Implementation of the Discovery Learning Model-Based Critical Thinking Skills in Thematic Learning at SDIT Al-Khairiyah - Ramadhanti, Enelsa; Nurhasanah, Ana; Taufik, M. (Universitas Pendidikan Indonesia Kampus Serang, 2023)
Critical thinking skills are one of the skills that elementary school students must possess. SDIT Al-Khairiyah differs from other schools since it has applied critical thinking skills using the discovery learning model. For this reason, the researchers are interested in researching this school to learn more about applying the discovery learning model based on critical thinking skills. This study thus aims to examine (1) planning, (2) implementation, and (3) evaluation of the implementation of the discovery learning model based on critical thinking skills in the thematic learning of class VB SDIT Al-Khairiyah. The method used was qualitative research, and the data used in this study were obtained through interviews with several sources (principal, teachers, and students), non-participatory observation, and documentation. The results of this study indicated that (1) the teacher prepared lesson plans by considering the characteristics of students and class conditions according to the stages of the discovery learning model. Teaching materials were adapted from learning objectives and learning media used, and then students’ worksheets were adapted from student books. (2) The implementation of the discovery learning model included stimulus, problem identification, data collection, data processing, evidence, and conclusions. (3) Class VB students seemed to have critical thinking skills. The characteristics that appeared in students consisted of logical and analytical thinking, having perspectives, actively asking questions, and having curiosity. These results can be examples of good practices to develop critical thinking skills using appropriate methods in elementary schools